Reversal of Stroke-Like Episodes With L-Arginine and Meticulous Perioperative Management of Renal Transplantation in a Patient With Mitochondrial Encephalomyopathy, Lactic Acidosis and Stroke-Like Episodes (MELAS) Syndrome. Case Report. (January 2022) - Al Yazidi, Ghalia; Mulder, Jaap; Licht, Christoph; Harvey, Elizabeth; Robertson, James; Sondheimer, Neal; Tein, Ingrid
Mitochondrial encephalomyopathy, lactic acidosis and stroke like episodes (MELAS) syndrome is a maternally inherited mitochondrial disorder with recurrent non-arterial distribution stroke-like episodes (SLEs). A 17 yr old boy with MELAS (m.3243A>G tRNA Leu(UUR) ) presented with SLEs at ages 8 and 10 yrs. At 11 yrs, he suffered a third SLE involving left parietotemporal lobes with dense right hemiplegia and aphasia persistent for 1 week without improvement. On high dose IV L-Arginine (L-Arg) (0.5 g/kg/day divided TID) he had rapid recovery within 48 hours and was rapidly weaned. With emesis of oral L-Arg, his SLE recurred and he was again treated with high dose IV L-Arg with similar rapid recovery and discharged on a slow wean over 6 wks to 0.1 g/kg/day. On maintenance L-Arg he suffered only 2 SLEs at ages 13 and 16 yrs; both resolved rapidly with high dose IV L-Arg without recurrence during a slow wean to maintenance. His phenotype included seizures, ptosis, ophthalmoplegia, facial diplegia, sensorineural hearing loss, ataxia, myopathy, exercise intolerance, peripheral sensorimotor neuropathy, hypertrophic cardiomyopathy, hypertension, and failure to thrive. At 16 yrs he developed end-stage renal disease, due to MELAS, requiring hemodialysis and at 17 yrs he underwent cadaveric renal transplantation. His peri-operative protocol included strict maintenance of perfusion, oxygenation, normothermia, biochemical homeostasis and serum arginine concentrations during which time there were no neurologic decompensations. He was transitioned to oral L-citrulline maintenance therapy which maintained higher serum arginine concentrations with better tolerance. He had no SLEs or seizures in the ensuing 2 yrs.